PENGARUH PENGGUNAAN DAUN KEMANGI DAN KULIT JERUK NIPIS PADA PROSES PENCUCIAN ALAT MAKAN TERHADAP ANGKA KUMAN - Safitri, Dewi; Yusmidiarti, Yusmidiarti; Wahyuni, Elly (JURNAL MEDIA KESEHATAN, 2013)
The process of washing utensils in the coto stall Minggu market still not meet the standard number of germs cutlery of allowed. Water used in the washing process is physically still do not meet the requirements because of water used repeatedly without being replaced in a day. These conditions could affect the health of consumers caused by washing utensils the lack of clean and unhygienic. Basil leaves and leather lime with the flavonoid and volatile oil can reduce the number of germs cutlery. Known effect of the use of basil leaves and leather lime in the process of washing utensils on the number of germs. Experimental studies with Posttest Only Control Group Design. Location of research conducted at the soup stall Minggu Market, of Ratu Samban District, City of Bengkulu. The subjects of this research is a leaf of basil (Ocimum sanctum) and the leather lime (Citrus aurantifolia). Research object is the number of germs cutlery. Test used is the One Way Anova. Research using 6 basil leaves and 1 small leather lime can reduce the number of germs cutlery. The One Way Anova test results are known significant value 0,028 < 0,05. This means that there are significant differences between the number of bacterial colonies the control group, basil and leather lime on the number of germs cutlery.